The associations among athlete gratitude, athlete engagement, athlete burnout: A cross-lagged study in China - Guo, Zhengmao; Yang, Jian; Wu, Ming; Xu, Yatao; Chen, Shuang; Li, Shouming (Frontiers in Psychology, 2022)
The purpose of this study is to explore the causal relationship among athlete gratitude, athlete engagement, athlete burnout by cross-lag analysis of longitudinal associations. Two questionnaire surveys were conducted on 352 Chinese athletes with an interval of 1 year using gratitude questionnaire, athlete engagement questionnaire and athlete burnout questionnaire. The analysis yielded four main findings. (1) The overall level of athlete gratitude and athlete engagement was high in China. Chinese athletes at master level had higher levels of gratitude and athlete engagement than athletes at I and II grades. (2)Athlete gratitude is a significant negative predictor of athlete burnout, and also a significant positive predictor of athlete engagement. (3) Athlete engagement and athlete burnout are mutually causal and can be mutually predicted. (4) Athlete gratitude indirectly affects athlete burnout through athlete engagement, and also indirectly affects athlete engagement through athlete burnout. The results of the current study demonstrated the important value of gratitude in the growth process of athletes, and clarified the mechanism of gratitude affecting athlete engagement and athlete burnout. These findings have important implications for athlete development by raising athlete gratitude, motivating athlete engagement levels and relieve athlete burnout.